Biomassa microbiana e degradação de serapilheira em pastos de tifton-85 manejados com índices de área foliar residual - Caputti, Gregory de Paula [UNESP] (2014)
The cycling of nutrients in pastures in Brazil is responsible for most of the nutrients entering the system, since the operating characteristics including low use of inputs. The aim of this study was to evaluate the decomposition of litter Cynodon spp. 85 hp Tfiton plied with residual leaf area indices grazed by sheep. Were evaluated by the decomposition of bags containing a known amount of litter during the following incubation times 0, 4, 8, 16, 32, 64, 128 and 256 days. The disappearance of dry mass were assessed, the behavior of nitrogen, phosphorus , carbon, addition of C:N. There was a higher rate of disappearance in the first 64 days of incubation followed by a slow phase until the end of the 256 days of incubation. There was an increase in the concentration of nitrogen and phosphorus during the study period